Effect of fringed rue (Ruta chalepensis) leaf as feed additives on growth performance and carcass characteristics of broiler chickens - Yonatan Kassu Yesuf; Abera Anja Zema; Melese Mengistu Mejab (Cogent Food & Agriculture, 2023)
AbstractRuta Chalepensis (fringed rue) has been used for therapeutic and aromatic purposes. However, using this plant as a natural additive in animals is scarce. A seven-week study was conducted to determine and elucidate the effects of fringed rue as a feed additive on broiler chickens growth performance and carcass characteristics. The average weight (40.08 ± 0.42 g) of 144 unsexed, day-old broiler chickens was arranged in a completely randomized design into four treatment groups. Each treatment group was divided into three replicates of twelve birds. Four treatments feed containing ground fringed rue leaves at different levels of T1 (basal diet+ the antibiotics Flavomycin at 1 g kg−1); T2 (basal diet + 60 g kg−1, T3 (basal diet + 120 g kg−1), and T4 (basal diet + 180 g kg−1. DM Intake was considerably high (P < 0.05) in the T3 group than in the antibiotics control group broilers. As a result, T3 groups have better improvement (P < 0.05) in final body weight, BW gain, and ADG compared to the antibiotics control in all phases. There were high improvements (P < 0.05) in dressing percentage, breast, thigh muscle, and drumsticks for chickens fed T3 and T2 than in the control group. Generally, supplementation of fringed rue up to 120 g kg−1 has no adverse effects on broiler chickens.